Coordination between growth, phenology, and carbon storage in three coexisting deciduous tree species in a temperate forest - Klein, Tamir; Vitasse, Yann; Hoch, Günter (My University, 2016)
n deciduous trees growing in temperate forests, bud break and growth in spring must rely on intrinsic carbon (C) reserves. Yet it is unclear whether growth and C storage occur simultaneously, and whether starch C in branches is suf cient for refoliation. To test in situ the relationships between growth, phenology and C utilization, we monitored stem growth, leaf phenology and stem and branch nonstructural carbohydrate (NSC) dynamics in three deciduous species: Carpinus betulus L., Fagus sylvatica L. and Quercus petraea (Matt.) Liebl. To quantify the role of NSC in C investment into growth, a C balance approach was applied. Across the three species, >95% of branchlet starch was consumed during bud break, con rming the importance of C reserves for refoliation in spring. The C balance calculation showed that 90% of the C investment in foliage (7.0–10.5 kg tree−1 and 5–17 times the C needed for annual stem growth) was explained by simultaneous branchlet starch degradation. Carbon reserves were recovered sooner than expected, after leaf expansion, in parallel with stem growth. Carpinus had earlier leaf phenology (by ∼25 days) but delayed cambial growth (by ∼15 days) than Fagus and Quercus, the result of a competitive strategy to ush early, while having lower NSC levels.